2002
DOI: 10.1152/ajpregu.00564.2001
|View full text |Cite
|
Sign up to set email alerts
|

ATP-stimulated Ca2+-activated K+ efflux pathway and differentiation of human placental cytotrophoblast cells

Abstract: The aim of this study was to determine whether extracellular ATP ([ATP]o) stimulated a Ca2+-activated K+ efflux in trophoblast cells that was dependent on extracellular Ca2+([Ca2+]o). Cytotrophoblast cells, isolated from human placenta, were examined following 18 h (relatively undifferentiated) and 66 h (multinucleate cells) of culture. Potassium efflux was measured using 86Rb as a trace marker. Intracellular Ca2+ ([Ca2+]i) was examined by microfluorometry using fura 2. [ATP]osignificantly increased 86Rb efflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…86 Rb efflux. 86 Rb efflux was assessed from cytotrophoblast cells under control conditions and in response to a panel of P2Y and P2X receptor agonists (2-MeS-ADP, 2-MeS-ATP, 5-BrUTP, ␣␤-meATP, ADP, ATP, BzATP, UDP, and UTP) using the methods previously described (12). Briefly, cytotrophoblast cells were loaded for 2 h with a 3 Ci/ml stock solution of 86 Rb in control Tyrode's solution (135 mM NaCl, 5 mM KCl, 1 mM MgCl2, 1.8 mM CaCl2, 5.6 mM glucose, and 10 mM HEPES, adjusted to pH 7.4 with 10 M NaOH) at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…86 Rb efflux. 86 Rb efflux was assessed from cytotrophoblast cells under control conditions and in response to a panel of P2Y and P2X receptor agonists (2-MeS-ADP, 2-MeS-ATP, 5-BrUTP, ␣␤-meATP, ADP, ATP, BzATP, UDP, and UTP) using the methods previously described (12). Briefly, cytotrophoblast cells were loaded for 2 h with a 3 Ci/ml stock solution of 86 Rb in control Tyrode's solution (135 mM NaCl, 5 mM KCl, 1 mM MgCl2, 1.8 mM CaCl2, 5.6 mM glucose, and 10 mM HEPES, adjusted to pH 7.4 with 10 M NaOH) at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…In an initial screening study, each agonist was applied at a single concentration (100 M) to cells isolated from the same placenta, to eliminate variability between placentas [our group previously found that 100 M ATP produced maximal 86 Rb efflux from cytotrophoblast cells (12)]. From these data, the rate constant of the fall in cellular isotope with time in controls was compared with that in the presence of each agonist on cells from the same isolate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…86 Rb efflux was measured in cytotrophoblasts at 66 h of culture using a technique previously described [53]. Briefly, cells plated onto 35 mm dishes were removed from the incubator and washed in control Tyrode’s buffer (135 mM NaCl, 5 mM KCl, 1.8 mM CaCl 2 , 1 mM MgCl 2 , 10 mM HEPES, 5.6 mM glucose, pH 7.4; osmolality ∼283 mOsm/kgH 2 O, isotonic compared to maternal plasma at term [56]; osmolality measured by freezing point depression).…”
Section: Methodsmentioning
confidence: 99%